A "snapshot" of physical activity and food habits among private school children in India. (November 2016) - Staab, Erin M; Cunningham, Solveig A; Thorpe, Sara; Patil, Shailaja S
Concerns about increasing obesity in poorer parts of the world, including India, have often been premised in terms of global shifts in activity levels and caloric consumption. Lifestyle changes have been documented in large cities, but we do not know whether these changes are reaching young people in less urban locations. This study used photo journals to explore children's perceptions of their food and activity habits in a remote Indian city. Children expressed interest in active pastimes, learning, and health, and indicated traditional, modern, local, and global influences in their lives. Findings offer context for research and interventions.